A study of technology in firewall system - Hamid Ali, Firkhan Ali (2011)
Firewall is a subject in form of hardware or software or both, which is use to protects a network from intrusion by outsiders. It is regulating the traffic that can pass through a router that connecting to the network infrastructure. It is preventing from unauthorized users to access the network whether from outside via the Internet or inside, Local Area Network (LAN) itself. Firewall system has many methods and techniques that imply and describes on each of their types or technologies. This paper had discussed about how all the methods in types of firewall functioning and give the advantages and disadvantages on decision making in a network security policy especially on using firewall system.